Social And Security Impact Of Covid-19 Outbreak In West Kalimantan Based On The Police Law Perspective - Yusuf Setyadi (Syariah: Jurnal Hukum dan Pemikiran, 2020)
AbstractThere is a dilemma in implementing social distancing as a government policy program to stay at home. For this, the author analyzed the police law perspective, especially the role of the National Police in overcoming the problems during the enactment of government regulations. The study was conducted using primary and secondary data. Primary data obtained through observation and interview, while secondary data obtained through library research. The data was then analyzed qualitatively and presented descriptively. From the results, it was concluded that the impact of the Covid-19 outbreak in the area of West Kalimantan Province was relatively safe and well-controlled which was indicated by no extraordinary crimes there. Polices had carried out their duties in all aspects both in maintaining security and public, law enforcement, protection, guard, and community services.Keywords: Social and Security Impacts; Police Law Perspective; Main Duties of Police. AbstrakAda dilema dalam pelaksanaan social distancing sebagai program kebijakan pemerintah untuk berdiam di rumah saja. Dalam menyikapi dilema tersebut, penulis menganalisis dalam perspektif hukum kepolisian. yaitu peran Polri dalam mengatasi permasalahan selama diberlakukannya peraturan pemerintah. Kajian dilakukan dengan menggunakan data primer dan data sekunder. Data primer didapatkan melalui pengamatan (observasi) dan wawancara di lapangan, sedangkan data sekunder didapatkan melalu penelitian kepustakaan. Data tersebut selanjutnya dianalisis secara kualitatif dan disajikan secara deskriptif. Dari hasil pembahasan disimpulkan bahwa dampak wabah Covid-19 di wilayah Provinsi Kalimantan Barat relatif aman dan terkendali dengan baik yang ditandai dengan tidak ada kejahatan luar biasa. Polri telah melakukan tugasnya dalam segala aspek baik dalam aspek pemeliharaan keamanan dan ketertiban masyarakat, dalam aspek penegakkan hukum, dan dalam aspek perlindungan, pengayoman dan pelayanan kepada masyarakat.Kata Kunci: Dampak Sosial dan Keamanan; Perspektif Hukum Kepolisian; Tugas Pokok Kepolisian